Inserção das competências socioemocionais na educação infantil: escola como agente formador de uma subjetividade reificada - Custódio, Caroline Cristine (Universidade Federal de São Carlos, 2024)
The research aims to analyze the integration of social emotional learning (SEL) in the Brazilian educational context, specifically in early childhood education from the turn of the 21st century. The investigation seeks to understand the theoretical foundations that support SECs, originating from American psychology and economics since the 1990s; analyze how emotional development is understood from the perspective of SEL and its implications for human development; and comprehend, from the framework of historical-cultural psychology, how psychological development actually occurs and its interrelation with affective aspects. To achieve this, the research employs historical-dialectical materialism as its analytical methodology and uses methodological procedures such as a bibliographic survey of works addressing the incorporation of SEL as a curricular component in Brazilian education; an examination and analysis of changes in legislation that regulate teaching in Brazilian schools, such as the Base Nacional Comum Curricular (National Common Curricular Base) (BRAZIL, 2017); a survey and analysis of documents from Multilateral Organizations (MOs) that present guidelines for education and contest their meaning; and a bibliographic review of contributions from historical-cultural psychology to think about psychological development and the affective-cognitive unity of the psyche. By utilizing contributions that analyze the relationship between work and education, the research concludes that the theory of SEL and their integration into education represent a theoretical and practical movement driven by new forms of economic reproduction that impact the world of work and the organization of life in society as a whole. In the face of a complex and interconnected set of social transformations, SEL in early childhood education emerge—along with other mechanisms—as a pragmatic and political response aimed at interfering with and transforming the psychological development of children, ultimately to resign them to the social status quo.
Incorporating social emotional learning in early childhood education: school as an agent for shaping reified subjectivity
Keywords: Competências socioemocionais; Unidade afetivo-cognitiva; Psicologia histórico-cultural; Alienação; Subjetividade; Social emotional learning; Affective-cognitive unity; Historical-cultural psychology; Alienation; Subjectivity; CIENCIAS HUMANAS::EDUCACAO::FUNDAMENTOS DA EDUCACAO